EXISTENCIA DE SOLUÇÃO PARA PROBLEMAS ENVOLVENDO O OPERADOR p-LAPLACIANO. - PEREIRA, William Luís Lima (2018)
In this work, we establish the existence of a solution to the class of problems involving the p-Laplacian operator. For this, we use classic results of Functional Analysis and Partial Differential Equations, in the order the established Mountain Pass Theorem.